Quality Momentum : Evidence from Nordic Stock Markets - Kontkanen, Katrin (My University, 2022)
Multi-factor investing has gained wide attention in recent years from both investors and researchers. Prior research on multi-factor investing has found that combined strategies outperform single-factor strategies. Given the increased attention towards this field the primary objective of this study is to examine multi-factor investing in the context of momentum and quality, measured by profitability, in the Nordic stock markets from 1996 to 2020. Gross profitability has been suggested as the cleanest measure of profitability in prior research that outperforms other profitability measures in the power of predicting future returns. Furthermore, operating profitability and later an extension to operating profitability that amends it as a cash-based measure have challenged the position of gross profitability as a profitability measure with the most predicting power of future returns. Previous studies have concluded that combining gross profitability and momentum factors into a joint strategy provides excess returns in the U.S. stock markets. The scope for this study consists of Nordic stock markets including Finland, Sweden, Norway and Denmark. The purpose is to investigate the possibility of combining momentum and quality into a joint strategy and if exploiting a joint strategy enhances the performance compared to the Nordic Market index and single-factor strategies formed solely based on momentum and quality. The portfolios in this study are formed as long-only and as long-short portfolios, and quality in this study is measured by three profitability factors: gross profitability, operating profitability and cash-based operating profitability. This study contributes to the existing literature of multi-factor investing by providing evidence of a multi-factor strategy returns in the Nordic stock markets. In addition, it adds to the field of quality investing by comparing the performance of the different profitability measures in the Nordic stock markets. The results suggest that a joint strategy increases the performance of a portfolio compared to a single-factor portfolio during the sample period in the Nordic stock markets. The performance of the joint strategies is the highest when momentum is joint with gross profitability or cash- based operating profitability as a long-short portfolio. Combining the two factors, by utilizing either gross profitability or cash-based operating profitability as the quality measure, into a joint strategy offers investors excess returns and in addition a decreased risk compared to a portfolio based on solely momentum. The results propose that investors could increase their portfolio performance by accounting for quality of the underlying companies in addition to the past performance of the stock.
Keywords: security market; profitability; investments; strategies; portfolios; Nordic countries; investors; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; Master's Degree Programme in Finance